Penerapan Ergonomi pada Perancangan Mesin Pewarna Batik untuk Memperbaiki Postur Kerja - Siswiyanti; Rusnoto (Jurnal Optimasi Sistem Industri, 2018)
The process of batik tulis (hand-waxed batik) dying in Kalinyamat Wetan, Tegal Municipality is performed in stooping and squatting working postures. Workers’ both hands hold a cloth and dip the cloth into a bucket containing colorants. When this dip dyeing process proceeds continuously for an enormous number of cloths, it will eventually result in musculoskeletal complaint, particularly in the such parts of body as the back, neck, leg, upper arm, lower arm and wrist. This research aims at designing an ergonomic batik dying machine to enable a natural body posture at work. The research anthropometry data and Rapid Entire Body Assessment (REBA) method. The research on batik craftswomen’s working posture during the traditional dip dyeing process found that the stooping and squatting worker’s posture scores are 4-8 with medium to high musculoskeletal levels (needs to needs to be immediately corrected). Meanwhile, the machine dip dyeing work position with standing body posture scores are 2-4 with safe to low musculoskeletal level (maybe need to be corrected in longer term). As for the specification of batik dyeing machine, it uses driving force of 0.190 HP, machine rotation of 72.5 rpm.